Basic sewing - Jefferys, Chris; DK Publishing, Inc. (New York : DK Pub., 1997)
Presents 101 illustrated sewing tips, with step-by-step instructions for attaching buttons, mending tears, working with patterns, and stitching by hand or machine.
Includes index.
Young Adult
Keywords: Dressmaking; Machine sewing; Sewing; Dressmaking; Sewing